Effectiveness of a telephone-based intervention for smoking cessation in patients with severe mental disorders: study protocol for a randomized controlled trial - Ballbè, Montse; Martínez, Cristina; Feliu, Ariadna; Torres, Núria; Nieva, Gemma; Pinet, Cristina; Raich, Antònia; Mondon, Sílvia; Barrio, Pablo; Hernández-Ribas, Rosa; Vicens, Jordi; Costa, Sílvia; et al. (Current controlled trials in cardiovascular medicine, 2019)
Background Up to 75% of inpatients with mental disorders smoke, and their life expectancy is decreased by up to 25 years compared to the general population. Hospitalized patients without monitoring after discharge quickly return to prehospitalization levels of tobacco use. The aim of the 061 QuitMental study is to assess the effectiveness of a multicomponent and motivational telephone-based intervention to stop smoking through a quitline addressed to smokers discharged from mental health hospital wards. Methods A pragmatic randomized controlled trial, single blinded, will include 2:1 allocation to the intervention group (IG) and the control group (CG). The IG will receive telephone assistance to quit smoking (including psychological and psychoeducational support, and pharmacological treatment advice if required) proactively for 12 months, and the CG will receive only brief advice after discharge. The sample size, calculated with an expected difference of 15 points on smoking abstinence between groups (IG, 20% and CG, 5%), α = 0.05, β = 0.10, and 20% loss, will be 334 participants (IG) and 176 participants (CG). Participants are adult smokers discharged from psychiatric units of five acute hospitals. Measurements include dependent variables (self-reported 7-day point prevalence smoking abstinence (carbon monoxide verified), duration of abstinence, number of quit attempts, motivation, and self-efficacy to quit) and independent variables (age, sex, and psychiatric diagnoses). In data analysis, IG and CG data will be compared at 48 h and 1, 6, and 12 months post discharge. Multivariate logistic regression (odds ratio; 95% confidence interval) of dependent variables adjusted for potential confounding variables will be performed. The number needed to treat to achieve one abstinence outcome will be calculated. We will compare the abstinence rate of enrolled patients between groups. Discussion This trial evaluates an innovative format of a quitline for smokers with severe mental disorders regardless of their motivation to quit. If effective, the pragmatic nature of the study will permit transfer to routine clinical practice in the National Health System. Trial registration ClinicalTrials.gov, NCT03230955 . Registered on 24 July 2017.